Russia’s Failure as a Benign Hegemon: The Domination of Hobbesian Culture in the 2008 Russo-Georgian War - Syawfi, Idil; Cahyadi, Robby (Global: Jurnal Politik Internasional, 2021)
This paper aims to explain the advent of the 2008 Russo-Georgian war. It is an important question to answer due to the historical, cultural, and economic relations between the two states, as well as Russia’s aspiration as a benign hegemon should have prevented the war from happening. The fact that two closely related ex-Soviet states went to war against each other points to a fundamental problem in their relationship that could happen to other states with similar preconditions, such as Ukraine, Azerbaijan, Armenia, Moldova, and more. In order to address this issue, Wendtian Constructivism is used to analyse the social interaction, key events, and the culture of anarchy that led to open warfare. This paper mainly relies on official documents and previous research as the primary sources, using news and media coverage to validate truths and opinions on key events. Based on that, this paper finds that: 1) social interaction between the two states was consistent with the Hobbesian culture of anarchy; 2) Russia’s aspiration as a benign hegemon failed to reproduce itself due to rejection from Georgia and their success in balancing Russia with the U.S., giving Georgia the capabilities to resist Russian narratives; 3) Georgia’s confrontative behaviours led to reciprocal actions from Russia, and; 4) the Georgian offensive on Tskhinvali was the trigger that confirmed the suspicions from both sides, making both countries decision to be based on the logic of enmity.